OPTIMIZING RESOURCES THROUGH NOTEBOOKLM TRAINING: TRANSFORMING ISLAMIC RELIGIOUS EDUCATION AT MTSN 1 PALEMBANG - Rahmawati Syamsoeri; Farah Hasanah Noor; Muhammad Sirozi (Jurnal Konseling Pendidikan Islam, 2026)
Digital transformation in education requires teachers to adapt to technological advancements. However, in practice, some Islamic Education (PAI) teachers still rely on lecture-based methods that are less interactive, despite the availability of digital facilities. This study aims to analyze training in the use of NotebookLM as a strategy to optimize resources in the management and development of educational institutions. This research employed a qualitative approach with a case study design using observation, interviews, and documentation. The findings indicate that the training enhances teachers’ digital competencies, optimizes the utilization of human, technological, physical, and organizational resources, and promotes more interactive learning. However, the transformation remains at the level of improving instructional practices and has not yet fully achieved deep learning transformation.